2017
DOI: 10.1080/13854046.2016.1278040
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of successful and unsuccessful simulators coached to feign traumatic brain injury

Abstract: Results contribute to a limited body of research investigating strategies utilized by individuals instructed to feign neurocognitive impairment. Findings signal the importance of developing additional embedded PVTs within standard cognitive tests to assess performance validity throughout a neuropsychological assessment. Future research should consider specifically targeting embedded measures in visual tests sensitive to slowed responding (e.g. response time).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…More recently, Kanser et al (2020) demonstrated that measuring eye behavior may enhance assessment of performance validity. Relying on previous literature on eye movements as reliable biomarkers of unconscious cognitive processes (Barry & Ettenhofer, 2016;Cook et al, 2012;Griffin & Oppenheimer, 2006;Kanser et al, 2017;Vrij et al, 2011), the authors examined the incremental utility of eye behavior on PVTs in discriminating between people who suffered Traumatic Brain Injury (TBI) and people coached to feign cognitive impairment. Their findings, consistent with previous literature, support the idea that oculomotor behavior improves deception detection, distinguishing deceptive from honest responding in experimental paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kanser et al (2020) demonstrated that measuring eye behavior may enhance assessment of performance validity. Relying on previous literature on eye movements as reliable biomarkers of unconscious cognitive processes (Barry & Ettenhofer, 2016;Cook et al, 2012;Griffin & Oppenheimer, 2006;Kanser et al, 2017;Vrij et al, 2011), the authors examined the incremental utility of eye behavior on PVTs in discriminating between people who suffered Traumatic Brain Injury (TBI) and people coached to feign cognitive impairment. Their findings, consistent with previous literature, support the idea that oculomotor behavior improves deception detection, distinguishing deceptive from honest responding in experimental paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…The present study contributed to the literature by examining exclusively non-memory RBANS subtests (i.e., those assessing attention, visuospatial ability, and language) in the context of noncredible performance using an analog simulation study. Given the high rate of noncredible responding in persons presenting for neuropsychological assessment secondary to mTBI (Larrabee et al, 2009;Young, 2015), making use of commonly administered neuropsychological tests to simultaneously assess test engagement/performance validity is practical, efficient, and clinically useful (Boone, 2009;Kanser et al, 2017;Meyers et al, 1999). Extensive previous literature has suggested that tests of attention (including tests N = 72.…”
Section: Discussionmentioning
confidence: 99%
“…Much previous literature has documented the preponderance and widespread contemporary use of standalone and embedded PVTs using memory-based paradigms (Martin, Schroeder, & Odland, 2015;Martin et al, 2019;Sharland & Gfeller, 2007), and readers are referred to extensive previous literature that has examined, critiqued, and summarized the utility of the extant RBANS PVTs (i.e., EI; Silverberg et al, 2007;ES;Novitski et al, 2012;PVI and CRIER;Paulson et al, 2015; see Goette & Goette, 2018;Shura et al, 2018), all of which include scores from one or more memory-based subtests. Notably, experimental work has articulated that memorybased paradigms may insufficiently detect simulated symptoms across other domains (e.g., Dandachi-FitzGerald & Merckelbach, 2012) and that overt memory impairment may be less frequently demonstrated in more sophisticated noncredible performance (Kanser et al, 2017), with extensive literature supports investigating tests of diverse cognitive abilities as indicators of noncredible performance (Boone, 2009;Victor et al, 2013). While all previous RBANS PVTs have included DS (which has shown to dissociate from RBANS memory subtests in factor analytic work; Emmert et al, 2018;Schmitt et al, 2010) in their calculations, they nonetheless capitalize on poor memory performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialized assessment tools have been developed to detect deception, and they work reasonably well, but outside of legal contexts, evaluators rarely use them (see Harrison, 2015, for discussion). Even observing a student work unusually slowly is likely to be interpreted by an evaluator as a sign of a genuine deficit in information processing speed (e.g., Braaten & Willoughby, 2014) or else as a desire to work carefully and to do well , even though working slowly is actually one of the most common strategies for fraudulently obtaining diagnoses (Kanser et al, 2017). The recent scandal should draw attention to deliberate underperformance on diagnostic tests—a phenomenon that has been documented in adolescents in a variety of contexts (e.g., avoiding returning to athletic participation after concussions, assisting family in obtaining disability payments, seeking access to stimulant medications; see Baker & Kirkwood, 2015).…”
Section: Learning Disability Identificationmentioning
confidence: 99%